Augmented Reality for ship bridges in Arctic Operations, a Virtual Reality experiment ... - Fjeld, Morten; Sætrevik, Bjørn; Nordby, Kjetil; Van Den Oever, Floris (OSF Registries, 2021)
For safety in ship operations, it is crucial to have high-quality collaboration between bridge crew members. Key components of that collaboration are situation awareness and communication. Augmented Reality has the potential to improve both. Besides that, the usability and potential risks and advantages of Augmented Reality for ship bridges must be understood before it is implemented. Therefore, we ask the following research questions: 1. Can Augmented Reality improve the situation awareness of ship bridge operators? 2. Does situation awareness related communication of ship bridge operators change when adding Augmented Reality to the ship bridge? 3. What is the perceived usability of these Augmented Reality systems for ship bridges? 4. What are perceived risks and advantages of these Augmented Reality systems for ship bridges? To answer these questions, we will conduct an experiment in which participants experience two arctic maritime scenarios in Virtual Reality from the vantage point of the ship bridge, ...